A Development of Marketing Strategies for Exporting; a Case of Face Skin Care Products Mixed with Virgin Coconut Oil - Sorat Mongkolmafai , Wannaree Pansiri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The objectives of this research were 1) to study marketing strategies on Marketing Mix strategy, Competitive Advantage Strategy, Technology Strategy, and Technology and Innovation Strategy for exporting in case of facial skin care products containing virgin coconut oil as an ingredient and 2) to study problems and obstacles or suggestions on marketing strategies for exports. The sample consisted of 350 employees who served in a company that has a facial care product containing virgin coconut oil as an ingredient. The research tool was a questionnaire. The statistics used to analyze the data were frequency, percentage, and standard deviation. The statistic used to test the research hypothesis was to find the correlation coefficient in order to analyze the correlation between exports of virgin coconut oil skin care products and marketing development strategies. Moreover, multiple regression analysis was used to create forecast equations for marketing strategies for the export of facial skin care products containing virgin coconut oil as an ingredient. The results showed that marketing mixed strategy, competitive advantage strategy, and technology and innovation strategy were associated with exports with a statistically significant level at 0.05. The output has a forecast efficiency of (R2=.385)38.5%.